A review of planting principles to identify the right place for the right tree for 'net zero plus' woodlands: Applying a place‐based natural capital framework for sustainable, efficient and equitable (SEE) decisions. Issue 2 (8th May 2022) - Bateman, Ian J.; Anderson, Karen; Argles, Arthur; Belcher, Claire; Betts, Richard A.; Binner, Amy; Brazier, Richard E.; Cho, Frankie H. T.; Collins, Rebecca M.; Day, Brett H.; Duran‐Rojas, Carolina; Eisenbarth, Sabrina; et al.
Abstract: We outline the principles of the natural capital approach to decision making and apply these to the contemporary challenge of very significantly expanding woodlands as contribution to attaining net zero emissions of greenhouse gases. Drawing on the case of the UK, we argue that a single focus upon carbon storage alone is likely to overlook the other 'net zero plus' benefits which woodlands can deliver. A review of the literature considers the wide variety of potential benefits which woodlands can provide, together with costs such as foregone alternative land uses. We argue that decision making must consider all of these potential benefits and costs for the right locations to be planted with the right trees. The paper closes by reviewing the decision support systems necessary to incorporate this information into policy and decision making. Read the free Plain Language Summary for this article on the Journal blog. Abstract : Read the free Plain Language Summary for this article on the Journal blog.